Client Choice May Provide an Economic Incentive for Veterinary Practices to Invest in Sustainable Infrastructure and Climate Change Education - Deluty, Sarah B.; Scott, Danielle M.; Waugh, Sabrina C.; Martin, Veronica K.; McCaw, Katherine A.; Rupert, Jessica R.; Webb, Tracy L.; Baumgarn, Stacey A.; Carpenter, Molly J.; Duncan, Colleen G. (Frontiers in Veterinary Science, 2021)
Objective: To assess how pet owners perceive the role of veterinary medicine in addressing climate change and animal health and determine if there is a client-driven economic incentive to establish sustainable veterinary business practices. Sample: 1044 dog and/or cat owners residing in the United States who had used veterinary services within the last three years. Procedures: An online Amazon mTurk survey about climate change and the perceived effects on client-owned dogs and cats was distributed to pet owners. Results: Most respondents believe climate change is occurring, and two-thirds of pet owners would value knowing their veterinarian received training on the animal health impacts of climate change. Over half of the respondents would pay more for veterinary services at a clinic with a reduced environmental impact. Additionally, clients would value some form of sustainability certification to aid in identification of such practices. Demographic influences found to be statistically significant included age, political ideology and where one resides (i.e. urban, suburban or rural) whereas gender and income level, were not found to be significant. Conclusions and Clinical Relevance: Our data suggest there is an economic incentive for veterinary professionals to be knowledgeable about the health impacts of climate change and to implement and market sustainable practice initiatives. Prioritizing sustainable practice initiatives and climate change education in veterinary practices has the potential to mutually benefit both practitioner and client through shared patient health and financial incentives.